The Structural of Effective Materials Management Factors Model: A PLS-SEM Approach - Kasim, Narimah Binti; Mat Jusoh, Zairra; Dodo, Mansir (International Journal of Sustainable Construction Engineering and Technology, 2021)
Effective materials management has a significant role in the success of any construction projects. Understanding the factors related to the management effectiveness may assist the decision-makers of construction firms to allocate resources in the best possible manner in managing materials when implementing construction projects. However, limited studies have explored and investigated the associated factors of effective materials management related to project performance, especially in the Malaysian construction industry context. Thus, this research paper aims to investigate the influential factors of effective materials management and their effects on project performance. A partial least square-structural equation modelling (PLS-SEM) approach was employed to analyse 202 pieces of data collected from a questionnaire survey. The results indicate that the effective materials management has a positive significant impact on project performance. The top three groups of factors that contribute to this management effectiveness are transportation, management, and purchasing; meanwhile, the most implied factors of the effective materials management are waste, cost and time of project performance. To increase project performance, more resources should be allocated to improve the transportation, management and purchasing components of materials management.